2014
DOI: 10.1016/j.chembiol.2014.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CDP-Archaeol Synthase, a Missing Link of Ether Lipid Biosynthesis in Archaea

Abstract: Archaeal membrane lipid composition is distinct from Bacteria and Eukarya, consisting of isoprenoid chains etherified to the glycerol carbons. Biosynthesis of these lipids is poorly understood. Here we identify and characterize the archaeal membrane protein CDP-archaeol synthase (CarS) that catalyzes the transfer of the nucleotide to its specific archaeal lipid substrate, leading to the formation of a CDP-activated precursor (CDP-archaeol) to which polar head groups are attached. The discovery of CarS enabled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 54 publications
1
75
0
Order By: Relevance
“…The presence of ancestral sequences for both superfamilies in the LUCA followed by the creation of G1PDH-and glycerol-3-phosphate dehydrogenase-specific clades thereof in the ancestors of Archaea and Bacteria, respectively, supports the scenario whereby domain-specific lipids arose through differential gene loss (10). This is also supported by the broad presence of CDP-alcohol phosphatidyltransferases, which catalyze the addition of polar headgroups (serine, glycerol, and myo-inositol) to produce intact phospholipids in both prokaryotic domains (60 -62), and suggests that at least one ancestor of CDP-based phospholipid synthesis was present in the LUCA (10,62,63). Biochemical and phylogenomic analyses have suggested that isoprenoids and fatty acid synthesis genes might have been present in the LUCA (10,50,64).…”
Section: Discussionmentioning
confidence: 53%
“…The presence of ancestral sequences for both superfamilies in the LUCA followed by the creation of G1PDH-and glycerol-3-phosphate dehydrogenase-specific clades thereof in the ancestors of Archaea and Bacteria, respectively, supports the scenario whereby domain-specific lipids arose through differential gene loss (10). This is also supported by the broad presence of CDP-alcohol phosphatidyltransferases, which catalyze the addition of polar headgroups (serine, glycerol, and myo-inositol) to produce intact phospholipids in both prokaryotic domains (60 -62), and suggests that at least one ancestor of CDP-based phospholipid synthesis was present in the LUCA (10,62,63). Biochemical and phylogenomic analyses have suggested that isoprenoids and fatty acid synthesis genes might have been present in the LUCA (10,50,64).…”
Section: Discussionmentioning
confidence: 53%
“…Purification and enzymatic assay of the NIOZ-UU3 GGGP synthase was based on the method of Jain et al 70 . E. coli BL21(DE3) harboring pABW4 was cultured in 250 mL Lysogeny broth Co-expression of GGGP and DGGGP synthases in E. coli.…”
Section: Recombinant Production Purification and In Vitro Enzyme Assmentioning
confidence: 99%
“…However, the expression level of the enzyme was either too low to detect ( Lai et al, 2009 ) or not investigated ( Yokoi et al, 2012 ). In a later study, a higher expression level of DGGGP synthase of Archaeoglobus fulgidus was obtained in E. coli by changing the ribosome-binding site and the activity of purified DGGGP synthase was monitored ( Jain et al, 2014 ).…”
Section: Biosynthesis Of Archaeal Membrane Lipidsmentioning
confidence: 99%